Hedge Fund industry : Developments and Practices. (Global Financial Stability Report; Global Financial Stability Report, 2004)
This paper analyzes developments in the hedge fund industry. The significant growth of hedge funds, driven by institutional investors, has heightened the desire by the official sector to better understand hedge funds and their activities. The paper examines how one may achieve a better understanding of hedge funds and their market activities, particularly for financial stability considerations. The paper reviews and updates developments in the hedge-fund industry since the previous IMF study in 1998, and considers what progress has been made to satisfy various recommendations and proposals from that time.